Incidental Diagnostic and Treatment of a Suppurative Appendicitis at Colonoscopy - Mohammed Amine Benatta (Case Reports in Medicine)
We herein report a patient with acute appendicitis who was diagnosed by colonoscopy: a 54-year-old woman with normal physical examination and laboratory results within normal limits. The case had shown an erythematous and edematous bulging polypoid lesion with purulent discharging from appendiceal orifice into the cecum. At colonoscopy, appendix appeared as an erythematous and edematous bulging polypoid lesion with purulent discharging from appendiceal orifice into the coecum. Surgeons exclude any emergency. Two weeks later, a colonoscopic second look was performed, and the same bulging polypoid lesion was found but without spontaneous purulent discharging. Appendiceal endoscopic pus drainage was then performed.